Current efforts in regional climate planning: A dataset from Italian NUTS2 regionsMendeley Data - Luigi Santopietro; Filomena Pietrapertosa; Angela Pilogallo; Monica Salvia (Data in Brief)
This data article provides a comprehensive description of climate change mitigation and adaptation policies implemented by 21 Italian regions (NUTS2 level) as of January 2024. It was developed as part a wider research work published by the authors [2].The dataset collects information on the efforts the regions are making to tackle the climate crisis. In particular, it contains a collection of regional climate plans (RCPs) and a catalogue of their contents analysed with regard to objectives, planned actions and monitoring and evaluation indicators.To complete the regional framework, the dataset also provides an overview of the socio-economic data for the Italian regions, derived from EUROSTAT (as of 2023), and the climate indicators from the Italian CIRO (Climate Indicators for Italian Regions) database, updated to 2021. Regional sustainable development strategies were also examined for consistency with climate planning and climate emergency declarations.Moreover, specific data are presented on the regions' participation in transnational networks and initiatives, as well as references on climate legislation currently in force (January 2024).